2008
DOI: 10.1200/jco.2007.10.8332
|View full text |Cite|
|
Sign up to set email alerts
|

Combination Targeted Therapy With Sorafenib and Bevacizumab Results in Enhanced Toxicity and Antitumor Activity

Abstract: Combination therapy with sorafenib and bevacizumab has promising clinical activity, especially in patients with ovarian cancer. The rapidity and frequency of sorafenib dose reductions indicates that sorafenib at 200 mg twice daily with bevacizumab 5 mg/kg every 2 weeks may not be tolerable long term, and alternate sorafenib dosing schedules should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
214
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(226 citation statements)
references
References 25 publications
6
214
1
5
Order By: Relevance
“…The pharmacodynamic interactions demonstrated that the tolerable dose of bevacizumab used is half or less of the recommended dose in other solid tumour studies (Azad et al, 2008b). We were unable to escalate beyond 5 mg kg À1 every 2 weeks because of proteinuria (n ¼ 2), thrombocytopaenia (n ¼ 1), and hypertension in DL 5A (n ¼ 2).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The pharmacodynamic interactions demonstrated that the tolerable dose of bevacizumab used is half or less of the recommended dose in other solid tumour studies (Azad et al, 2008b). We were unable to escalate beyond 5 mg kg À1 every 2 weeks because of proteinuria (n ¼ 2), thrombocytopaenia (n ¼ 1), and hypertension in DL 5A (n ¼ 2).…”
Section: Discussionmentioning
confidence: 96%
“…There was a 6-week accrual pause between DLs to monitor for delayed toxicity. A history, blood pressure measurement, and urine protein/creatinine ratio were performed before each bevacizumab dose, with detailed history and physical examination every cycle (Azad et al, 2008b). If the urine protein/creatinine ratio was greater than 1.0 but less than grade 3, bevacizumab was given and a 24-h urine was collected for measurement of protein before the next cycle.…”
Section: Treatment Planmentioning
confidence: 99%
See 1 more Smart Citation
“…All perforations occurred in patients who had received three or more chemotherapy regimens and there was a trend towards higher perforation rates in patients with documented bowel wall involvement or bowel obstruction at study entry. Bowel perforations and enteral fistulae have also been reported in other phase II trials utilising bevacizumab in advanced ovarian cancer (Azad et al, 2008;Garcia et al, 2008). However, no definitive conclusions on aetiological factors can be drawn, due to the small number of patients in each group.…”
Section: Toxicity With Vegf Inhibitorsmentioning
confidence: 93%
“…A phase I study of sorafenib and bevacizumab demonstrated durable partial disease responses (4 -22 þ months) in 6 of 13 ovarian cancer patients recruited. Toxicity appears higher than that with single-agent anti-VEGF therapy, with twothirds of the patients developing hypertension and 79% incidence of grade 1 -3 hand -foot syndrome (Azad et al, 2008). Enteral fistulae were also seen in 2 of the 13 ovarian cancer patients on study.…”
Section: Targeting the Vegf Pathway In Ovarian Cancermentioning
confidence: 98%